2018
DOI: 10.1177/0954407018758567
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of disengaged wet brake packs

Abstract: Key objectives in off-highway vehicular powertrain development are fuel efficiency and environmental protection. As a result palliative measures are made to reduce parasitic frictional losses, whilst sustaining machine operational performance and reliability. A potential key contributor to the overall power loss is the rotation of disengaged wet multi-plate pack brake friction. Despite the numerous advantages of wet brake pack design, during high speed manoeuvre in highway travel or at start-up conditions sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Subsequently, these measured losses are subtracted from the measurements taken with the sump (4) filled to the shaft centre line (representative of wet brake operating conditions). The sump (4) temperature is altered by a heating element (6), which is used in conjunction with a control unit and thermocouple to regulate the sump temperature.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, these measured losses are subtracted from the measurements taken with the sump (4) filled to the shaft centre line (representative of wet brake operating conditions). The sump (4) temperature is altered by a heating element (6), which is used in conjunction with a control unit and thermocouple to regulate the sump temperature.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The primary purpose of the rig is to measure the frictional drag losses under different operating conditions: temperature and sliding speed. A detail description of the test rig is also provided in Leighton et al 11 The rig comprises an electric motor (1), connected to an inline torque limiting coupling (2), rotatory torque transducer (3) and an immersed brake disc (5), rotating between the two stator discs (6). The rotatory torque transducer has a sampling rate of 450 Hz, maximum operation speed of 15,000 r/min and a sensitivity and operational torque range of 50 ± 0 . 05 Nm .…”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Leighton et al. 17 presented a Reynolds-based numerical model including the effect of fluid inertia and squeeze film transience for prediction of performance of wet brake systems. It was shown that cavitation becomes significant at low temperatures due to microhydrodynamic action, enhanced by high fluid viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Multibody vehicle dynamic model was built in multibody dynamic simulation software and suspension system, tire model, braking system, engine system, steer system, vehicle frame were included. Leighton et al 17 presented a Reynolds-based numerical model including the effect of fluid inertia and squeeze film transience for prediction of performance of wet brake systems. It was shown that cavitation becomes significant at low temperatures due to microhydrodynamic action, enhanced by high fluid viscosity.…”
Section: Introductionmentioning
confidence: 99%